Antioxidant and free radical scavenging activity of Spondias pinnata - Mandal Nripendranath; Biswas Santanu; Hazra Bibhabasu (BMC Complementary and Alternative Medicine, 2008)
Abstract Background Many diseases are associated with oxidative stress caused by free radicals. Current research is directed towards finding naturally-occurring antioxidants of plant origin. The aim of the present study was to evaluate the in vitro antioxidant activities of Spondias pinnata stem bark extract. Methods A 70% methanol extract of Spondias pinnata stem bark was studied in vitro for total antioxidant activity, for scavenging of hydroxyl radicals, superoxide anions, nitric oxide, hydrogen peroxide, peroxynitrite, singlet oxygen and hypochlorous acid, and for iron chelating capacity, reducing power, and phenolic and flavonoid contents. Results The extract showed total antioxidant activity with a trolox equivalent antioxidant concentration (TEAC) value of 0.78 ± 0.02. The IC50 values for scavenging of free radicals were 112.18 ± 3.27 μg/ml, 13.46 ± 0.66 μg/ml and 24.48 ± 2.31 μg/ml for hydroxyl, superoxide and nitric oxide, respectively. The IC50 for hydrogen peroxide scavenging was 44.74 ± 25.61 mg/ml. For the peroxynitrite, singlet oxygen and hypochlorous acid scavenging activities the IC50 values were 716.32 ± 32.25 μg/ml, 58.07 ± 5.36 μg/ml and 127.99 ± 6.26 μg/ml, respectively. The extract was found to be a potent iron chelator with IC50 = 66.54 ± 0.84 μg/ml. The reducing power was increased with increasing amounts of extract. The plant extract (100 mg) yielded 91.47 ± 0.004 mg/ml gallic acid-equivalent phenolic content and 350.5 ± 0.004 mg/ml quercetin-equivalent flavonoid content. Conclusion The present study provides evidence that a 70% methanol extract of Spondias pinnata stem bark is a potential source of natural antioxidants.